LGBT - San Francisco the Daniel Nicoletta photographs - Nicoletta, Daniel 1954-; Nourmand, Tony 1965-; Van Sant, Gus 1952- (RAP, Reel Art Press, 2017)
Something of a living legend, Daniel Nicoletta (born 1954) has been the leading chronicler of the LGBT civil rights movement in San Francisco over the last 40 years. This is the first book dedicated to his powerful photographs from the burgeoning lesbian-gay-bisexual-transgender mecca that was San Francisco in the 1970s and its journey to the present.0Nicoletta is best known for his iconic images of Harvey Milk, one of the world?s first openly gay elected officials, who was assassinated by a homophobic colleague in 1978. Nicoletta portrayed the glittering drag queens, the fabulous costumes, the alternative theater world and the quiet bravery of same-sex couples trying to live their lives. Today, Nicoletta continues to document the reverberations of Milk?s legacy. He serves as a key point person for LGBT civil rights and Milk-related research. In 2014, one of Nicoletta?s photographs was used on a Harvey Milk Forever stamp. 'LGBT: San Francisco' is an essential gay history and a stunning photographic work that is not to be missed
Keywords: Nicoletta, Daniel -- 1954-; Geschichte 1977-2015; Homosexuellenbewegung; Fotografie; San Francisco -- Calif., Motiv; Nicoletta, Daniel / 1954-; Gays / California / San Francisco / Portraits; Portrait photography / California / San Francisco; Documentary photography / California / San Francisco; Bildband